2010
DOI: 10.1590/s1679-87592010000700005
|View full text |Cite
|
Sign up to set email alerts
|

Faecal bacteria in Perna perna (Linnaeus, 1758) (Mollusca: Bivalvia) for biomonitoring coastal waters and seafood quality

Abstract: A B S T R A C TUrban development in coastal areas is intense and leads to the increase of sewage outfall and other negative impacts as consequences. Thus, stringent regulations establishing limits to the microbiological contamination of water and seafood are needed. The objective of this study is to evaluate the usefulness of Enterococci and Thermotolerant Coliform densities in the flesh of mussels Perna perna as an alternative tool for monitoring the microbiological quality of coastal waters. The study also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
1
6
0
6
Order By: Relevance
“…The same seasonal trend was found in the Thau Lagoon in France (Derolez et al 2013). Levels of thermotolerant coliforms in bivalve molluscs may differ with fecal contamination in the surrounding water (Martínez & Oliviera, 2010) and may change from one time period to another (Campos et al 2013a;Soegianto & Supriyanto, 2008). Derolez et al (2013) noted an inverse relationship between E. coli concentrations in seawater and in C. gigas oysters.…”
Section: Vega Corrales and Marín Vindasmentioning
confidence: 54%
“…The same seasonal trend was found in the Thau Lagoon in France (Derolez et al 2013). Levels of thermotolerant coliforms in bivalve molluscs may differ with fecal contamination in the surrounding water (Martínez & Oliviera, 2010) and may change from one time period to another (Campos et al 2013a;Soegianto & Supriyanto, 2008). Derolez et al (2013) noted an inverse relationship between E. coli concentrations in seawater and in C. gigas oysters.…”
Section: Vega Corrales and Marín Vindasmentioning
confidence: 54%
“…However, a study by Martinez & Oliveira (2010) obtained bacterial densities in mussel flesh from 50 to 4,300 times greater than in water sampled in the vicinity of the mussels, which indicated that the relationship between the number of bacteria in the water and the bacteria accumulated by the mollusks is not straightforward and depends on many, difficult to evaluate, factors. Bacterial densities found in mussels are the result of complex interactions related to their physiology and morphology, such as size, filtering, excretion, and metabolic rates (Solé et al, 2000), and also depend on prey characteristics, such as size, specific composition and density of bacteria in the water.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have highlighted the effect of temperature and salinity on physiological indicators (such as clearance and absorption efficiency) in shellfish species 10,23 . Another study observed that the clearance rate and absorption efficiency in mussels (Perna perna)…”
Section: Discussionmentioning
confidence: 99%